Mini-invasive resection and collapse therapy in patients with bilateral pulmonary tuberculosis - Korpusenko I.V. (Medičnì Perspektivi)
Objective. Improve the effectiveness of surgical treatment in patients with bilateral destructive pulmonary tuberculosis by mini-invasive resection and collapse therapy. Materials and Methods: Retrospective analysis of 222 patients’ cards with bilateral destructive pulmonary tuberculosis who were treated in the period from 1995 to 2014 in the thoracic department of Dnepropetrovsk regional clinical therapeutic and prophylactic association "Phthisiology". Patients were divided into 2 groups: basic (111 patients who underwent mini-invasive surgery) and control (111 patients, who underwent standard surgical approach). The distribution of patients in investigated groups was representative by the majority of parameters. Results and discussion. The average duration of simultaneous bilateral VATS lung resections was 1,90 ± 0,12 hour, standard thoracotomies - 2,13 ± 0,19 per hour, estimated blood loss was 234±5,20ml and 433±3,70ml respectively. The average postoperative time in-patient was 52,40±2,63 days in basic and 80,10±3,58 days in the control group. Number of postoperative complications after lung resection with VATS was significantly lower (1.6 times), as compared with standard surgical approach. Volume of blood loss less than 400 ml was 93,40±3,20% in basic and 72,60±4,80% in the control group, the amount of intraoperative complications reduced by 2.2 times. Complete clinical response (decontamination and closing of cavities) have been achieved in patients of the basic group by 1.6 times more often. Conclusions: For patients with bilateral pulmonary tuberculosis to perform mini-invasive surgical approach is the best option. Mini-invasive interventions with VATS due to its good abilities to visualize tissues and anatomical structures may significantly decrease the amount of intraoperative blood and plasma loss in the first postoperative day. It leads to the stabilization of tuberculosis process in the contralateral lung, responsible for overall positive clinical effect in patients with advanced pulmonary tuberculosis. For patients with bilateral destructive pulmonary tuberculosis, who can’t undergo resection, performing a mini-invasive therapeutic thoracoplasty is the optimal approach.